The bilateral effects of digital economy on regional carbon emissions in China - Liu, Chao; Wang, Wei; Ding, Chenhui; Teng, Xianzhong; Ye, Yuxin; Zhang, Zejing (Frontiers in Environmental Science, 2023)
The impacts of the digital economy on regional carbon emissions have attracted much concerns from all regions of China. Using panel data for 30 Chinese provinces and cities from 2011 to 2020, the study empirically examined the bilateral effects of the digital economy on regional carbon emissions (RCBs) and the heterogeneous characteristics under different conditions by various econometric models. The results indicate that, the inhibition effect of digital economy development on regional carbon emissions is stronger than the promotion effect, which is 13.38% lower and 12.11% higher than the frontier level respectively. When both effects are combined, it makes regional carbon emissions 1.27% below the frontier boundary. In addition, the inhibition effect of the digital economy on carbon emissions (DECEs) predominant and presents a declining trend during the study period. And the inhibition effect of the digital economy on carbon emissions in the eastern region is highest among all the regions. Moreover, the level of different factors such as digital economy, human capital and economic development, can effectively strengthen the inhibition effect of digital economy on regional carbon emissions. This work will be conducive to fully leveraging the important role of the digital economy in regional environmental governance in China, and promote the achievement of China’s carbon peaking and carbon neutrality goals.